Effect of sputtering rate on morphological alterations, corrosion resistance, and endothelial biocompatibility by deposited tantalum oxide coatings on NiTi using magnetron sputtering technique - Mahdiyeh Soltanalipour; Jafar Khalil-Allafi; Alireza Mehrvarz; Amir Kahaie Khosrowshahi (Journal of Materials Research and Technology, 2024)
The Magnetron sputtering method was utilized to apply tantalum-oxide coatings on NiTi shape memory alloys, and this was done under 16.6 vol% oxygen, 83.4 vol% argon atmospheres at a substrate temperature of 300 °C. In the present article, the influence of sputtering rate on surface morphology, roughness, corrosion behavior, and biological response of tantalum oxide coatings has been investigated via FESEM, AFM, potentiodynamic polarization method, and MTT assay, respectively. FESEM studies demonstrated the positive effect of sputtering rate on forming a uniform and dense layer under 0.8 Å s−1 sputtering rate. GI-XRD patterns depicted amorphous coatings in all samples, meaning 300 °C was not sufficient for the formation of crystallized TaxOy. The XPS results revealed that stoichiometric tantalum pentoxide formed at the top of the layer under 0.8 Å s−1 sputtering rate as there was enough oxygen to support the reaction. AFM 3D images of surface topographies suggested that all coatings possessed almost similar roughness values, but their line graphs showed irregular peaks and valleys for lower and higher sputtering rates. Electrochemical measurements indicated the expected results of supremacy in corrosion resistance for the sample sputtered under 0.8 Å s−1 with the most uniform morphology. Finally, the biocompatibility of the coatings was studied using specific human endothelial cells (HUVECs) to evaluate their potential for vascular applications. Unlike other results, the sample, which sputtered at the highest rate with lots of hills and valleys, showed the greatest cell viability and cellular activity on its surface.